Review paperReview of renal cell carcinoma with rhabdoid features with focus on clinical and pathobiological aspects - Kuroda, Naoto; Karashima, Takashi; Inoue, Keiji; Kasajima, Atsuko; Ohe, Chisato; Kawakami, Fumi; Mikami, Shuji; Matsuura, Keiko; Moriyama, Masatsugu; Nagashima, Yoji; Petersson, Fredrik; Lopez, Jose I.; et al. (Polish Journal of Pathology, 2015)
Rhabdoid morphology in renal cell carcinoma (RCC) may, like sarcomatoid change, be perceived as a type of dedifferentiation, and is a poor prognostic factor. Histologically, rhabdoid neoplastic cells are round to polygonal cells with globular eosinophilic cytoplasmic inclusions and eccentric vesicular nuclei and enlarged nucleoli. All types of RCC, including clear cell, papillary, chromophobe, collecting duct carcinoma, renal medullary carcinoma, acquired cystic disease-associated RCC, ALK-positive renal cancer and unclassified RCC, may display a variably prominent rhabdoid phenotype. Immunohistochemically, the cytoplasm of rhabdoid cells shows positivity for vimentin and/or cytokeratin. Ultrastructurally, cytoplasmic whorls/aggregates of intermediate filaments correspond to light microscopically observed inclusions. Genetically, a previous report suggests that combined loss of BAP1 and PBRM1 may be associated with rhabdoid morphology. As with sarcomatoid change, pathologists should describe, estimate and state the proportion of tumor cells with a rhabdoid phenotype in the routine pathology report of RCC.